Autonomy support, peer relations, and teacher-student interactions: implications for psychological well-being in language learning - Wu, Di; Dong, Xin (Frontiers in Psychology, 2024)
Introduction: This research explores the intricate interplay among teacher-student relationships, perceived autonomy support, peer relationships, and their collective impact on the psychological well-being of 387 university students enrolled in French language courses across diverse academic institutions in China. Methods: Employing Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM), this study aims to establish the validity and robustness of the proposed model. Data collection involved online surveys utilizing Likert scales and standardized measures to assess variables concerning educational relationships and psychological well-being.The findings reveal significant associations between teacher-student relationships, autonomy support, positive peer relationships, and psychological well-being. Importantly, analyses demonstrate the influential role of positive peer relationships in mediating the effects of teacher-student relationships and autonomy support on students' psychological well-being. Discussion: These outcomes emphasize the crucial significance of educational relationships in shaping students' psychological well-being within academic settings. The findings contribute to understanding the nuanced dynamics of educational interactions and their profound implications for student well-being. This highlights the necessity of cultivating positive educational environments for enhanced student mental health.